About the face and the expression: The edenic time as revolutionary - Taub, Emmanuel (2018)
From the biblical text to the Jewish Philosophy of the Twentieth Century, from Walter Benjamin and Emmanuel Levinasto the philosophy of Martin Heidegger and Giorgio Agamben, from Rilke’s poetry to the poetry of Paul Valéry, the problem of Face, expression and language have been a central topic of Jewish Thought. Among these problems, the discussion of sacred time and profane time becomes the place to think about the problem of Revelation. The main objective of this article is to analyze the Revelation from the perspective of Jewish Thought in relation to the language and problem of the divine Face. It will focus on this, by exploring the philosophy of Levinas and its connection with the biblical text, opening from there the reflection towards other authors in a friendly dialogue.